False Identity - Rusu, Ion (Journal of Danubian Studies and Research, 2022)
In this paper, I proceeded to examine the crime of false identity regarding the text of the act of incrimination. Thus, we analysed the subjects, as well as the objective and subjective side of the crime with direct reference to the recent judicial practice in the matter. We also highlighted the elements of similarity as well as those of differentiation between the texts of the two laws, the analysis being useful both from a doctrinal perspective and for the identification and application of the more favourable criminal law. The novelty elements consist in the analysis performed, with reference to the recent judicial practice, as well as in the citation of several authors from the Romanian doctrine. The paper is part of a university course to be published by a recognized publishing house in the field of legal sciences. By the way of approach, the paper can be useful to the students of the profile faculties in the country, as well as to the practitioners of the criminal law.